2018
DOI: 10.1016/j.chiabu.2018.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Promoting young children’s interpersonal safety knowledge, intentions, confidence, and protective behavior skills: Outcomes of a randomized controlled trial

Abstract: Promoting young children's interpersonal safety knowledge, intentions confidence and skills is the goal of many child maltreatment prevention programs; however, evaluation of their effectiveness has been limited. In this study, a randomized controlled trial was conducted examining the effectiveness of the Australian protective behaviors program, Learn to be safe with Emmy and friends™ compared to a waitlist condition. In total, 611 Australian children in Grade 1 (5-7 years; 50% male) participated, with assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…However, only one program was shown to have been rigorously evaluated using a quasi-experimental method (Michaelson, 2001). Subsequent to the data collection period, we are aware that one other program has been evaluated in a fully experimental randomized controlled trial (White, Shanley, Zimmer-Gembeck, Lines, Walsh, & Hawkins, 2016; White, Shanley, Zimmer-Gembeck, Walsh, Hawkins, & Lines, 2018; White, Shanley, Zimmer-Gembeck, Walsh, Hawkins, Lines, & Webb, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…However, only one program was shown to have been rigorously evaluated using a quasi-experimental method (Michaelson, 2001). Subsequent to the data collection period, we are aware that one other program has been evaluated in a fully experimental randomized controlled trial (White, Shanley, Zimmer-Gembeck, Lines, Walsh, & Hawkins, 2016; White, Shanley, Zimmer-Gembeck, Walsh, Hawkins, & Lines, 2018; White, Shanley, Zimmer-Gembeck, Walsh, Hawkins, Lines, & Webb, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous programs designed to address CM, many of which have promising results; likewise, there are some common limitations (Walsh et al 2015). As previously discussed, many CM prevention programs are single-harm focused, and may overlook other forms of CM (White et al 2018). The single-harm focus could represent a missed opportunity for improving child wellbeing and reducing CM.…”
Section: Introductionmentioning
confidence: 99%
“…The single-harm focus could represent a missed opportunity for improving child wellbeing and reducing CM. Given that single-harm focused programs often emphasize similar skills (e.g., identifying safe situations and developing interpersonal skills), integrating multiple prevention programs may be more efficient (White et al 2018). There is a tremendous need for programming related to neglect, as there are no manualized evidence-based school programs for the prevention of psychological effects of physical neglect (Brassard and Fiorvanti 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In five 1-hour sessions conducted in schools, this program includes the discussion of how to identify unsafe situations, how to identify unsafe secrets, and when, to whom, and how to disclose to adults. Past evaluations have found Learn to be safe with Emmy and friends ™ increases protective behaviors knowledge in children aged 5–7 years of age compared to children in waitlist classrooms (Dale et al, 2016) or schools (White et al, 2018b). Evaluations have also found that children improve over time in protective behaviors/disclosure intentions, disclosure confidence, and ability to identify unsafe situations (Dale et al, 2016; White et al, 2018b).…”
mentioning
confidence: 99%
“…Past evaluations have found Learn to be safe with Emmy and friends ™ increases protective behaviors knowledge in children aged 5–7 years of age compared to children in waitlist classrooms (Dale et al, 2016) or schools (White et al, 2018b). Evaluations have also found that children improve over time in protective behaviors/disclosure intentions, disclosure confidence, and ability to identify unsafe situations (Dale et al, 2016; White et al, 2018b). However, generally these improvements over time have not differed significantly between intervention and waitlist control groups.…”
mentioning
confidence: 99%